Differentiated Impact of AGOA and EBA on West African Countries - Coulibaly, Souleymane (World Bank, Washington, DC, 2021)
The African Growth Opportunity Act (AGOA) and Everything But Arms (EBA), two preferential agreements extended by the United States (AGOA) and the European Union (EU) (EBA) to some developing countries seem to have contributed somewhat to boost Sub-Saharan Africa’s exports since 2001. However, not all African countries have benefited from them, among which West African countries. Paradoxically, these latter countries host two of the most advanced regional economic communities in Sub-Saharan Africa: the West African Economic and Monetary Union (WAEMU) sharing a common monetary policy that has consistently maintained inflation low and forming a customs union with a compensation mechanism to uphold the common external tariff; and the economic community of West African States (ECOWAS) maintaining a regional military force (ECOMOG) and peer pressure that have rooted out military coups in its member countries. Simulations derived from a Pseudo Poisson maximum likelihood gravity model estimation show that West Africa could be exporting 2.5 to 4 times more to the EU and the US if AGOA and EBA were not implemented in a differentiated manner, in terms of country eligibility, product coverage, and rules of origins. Given such trade creation potential for a group of countries committed to deep regional integration, a revision of AGOA and EBA, or a special ECOWAS and WAEMU provision will make these preferential trade agreements a driving force behind the success of regional integration in Sub-Saharan Africa.